Modelagem estatística multivariada dos conceitos relacionados à física ambiental - Jorge Neto, Miguel (2014)
The natural environment where humankind is inserted and has modified through history is an open system and, therefore, complex. The consequent specializations within scientific knowledge has contributed to turn away basic sciences, like physics, biology and chemistry from the necessary dialogue to understand and describe environmental phenomena at global scale that manifest in these systems. In this scope, a new set of knowledge more suitable to study of environment has been structuring. To understand the role of Environmental Physics in these process, this work proposed to investigate the concepts and principles that underlie this science as from conceptions within groups that compose the academy. To achieve this, a triangulation between bibliographic references at electronic databases, interviews with field specialists and the production from Post Graduate Program at Environmental Physics (PPGFA/UFMT) was made. The results allowed us to identify a set of scientific knowledges that suggests the scope of the Environmental Physics, besides showing that its origin is intertwined with Agrarian Sciences and typical physics knowledges.